Implementation of Technology on English for Specific Purposes (ESP) Students in Communicative Language Teaching Approach - Sukmawati, Sukmawati; Syam, Nur Ina Syam; Jubhari, Yuriatson Jubhari; Mardiani, Mardiani; Sasabone, Luana; sujarwo, sujarwo (Universitas Cokroaminoto Palopo, 2023)
Students can prepare themselves to enter the global workforce by learning English for Specific Purpose (ESP) as communicative approach, which is a crucial part of the subject. One way to make learning ESP enjoyable for students so they will be driven to do and will be able to grasp the topic quickly is by using social media. This study aimed to analyze technology on English for specific purposes (ESP) students in communicative language teaching approach. This study applied qualitative method. The data collection techniques used are observation, interviews, and documentation. The triangulation technique as a data validity technique is carried out by comparing interview data with data obtained from observations and data from documentation. From the research conducted, it was found that the use of social media as a medium for learning ESP had a positive effect, namely, as a means of communication that is in high demand, as a tool for triggering student interaction and motivation, and as a collaborative tool. Implications for teaching ESP with the help of technology and suggestions for further research were also provided